Effects of pulmonary endarterectomy on pulmonary hemodynamics in chronic thromboembolic pulmonary hypertension, evaluated by interventricular septum curvature - Saito, Takahiko (Pulm Circ, 2020)
The interventricular septum curvature, measured in images of electrocardiogram-gated 320-slice multidetector computed tomography, is reportedly useful and less invasive than right heart catheterization, as it could provide clues regarding pulmonary arterial pressure in patients with chronic thromboembolic pulmonary hypertension. Although pulmonary endarterectomy is an efficient treatment for chronic thromboembolic pulmonary hypertension, the interventricular septum curvature in patients who have received pulmonary endarterectomy has not been evaluated. We evaluated whether the interventricular septum curvature on electrocardiogram-gated 320-slice multidetector computed tomography can predict pulmonary hemodynamics in chronic thromboembolic pulmonary hypertension even after pulmonary endarterectomy. We studied 40 patients with chronic thromboembolic pulmonary hypertension (60.5 ± 9.7 years; 30 females), who underwent pulmonary endarterectomy at Chiba University Hospital between December 2010 and July 2018. To measure the interventricular septum curvature, we prepared left ventricular short-axis tomographic images from 4D images of electrocardiogram-gated 320-slice multidetector computed tomography. We calculated the radius of interventricular septum and determined the interventricular septum curvature in both the systolic and diastolic phases. We compared the interventricular septum curvature with pulmonary hemodynamics measured by right heart catheterization before and after pulmonary endarterectomy. After pulmonary endarterectomy, the correlations of the interventricular septum curvature with mean pulmonary arterial pressure, systolic pulmonary arterial pressure, and pulmonary vascular resistance disappeared, although the interventricular septum curvature was correlated with these pulmonary hemodynamic parameters before pulmonary endarterectomy. Changes in systolic interventricular septum curvature revealed significant correlations with changes in mean pulmonary arterial pressure, systolic pulmonary arterial pressure and pulmonary vascular resistance. Diastolic interventricular septum curvature also showed significant correlations with preoperative pulmonary hemodynamics, but not with postoperative pulmonary hemodynamics. Changes in the interventricular septum curvature after pulmonary endarterectomy could estimate the efficacy of pulmonary endarterectomy, although the interventricular septum curvature after pulmonary endarterectomy showed no significant correlations with pulmonary hemodynamics. Additionally, our findings confirmed that the interventricular septum curvature before pulmonary endarterectomy could be used to evaluate the severity of disease.